Evaluation of Ankle Swelling Due to Lofgren's Syndrome: A Pilot Study Using B‐Mode and Power Doppler Ultrasonography. Issue 2 (February 2014) - Le Bras, E.; Ehrenstein, B.; Fleck, M.; Hartung, W.
<x xml:space="preserve">Abstract</x> Objective Patients with acute sarcoidosis frequently present with bilateral painful swelling of the ankles, establishing ankle arthritis as a hallmark of Lofgren's syndrome. Standardized high‐resolution musculoskeletal ultrasound (MSUS), including power Doppler, has been utilized to further characterize the nature of ankle swelling in patients presenting with Lofgren's syndrome. Methods The ankle joints of 36 consecutive patients with Lofgren's syndrome were investigated by high‐resolution MSUS using B‐mode and power Doppler mode. The presence of effusion/synovitis and tenosynovitis was determined, and hyperperfusion was scored in a semiquantitative fashion (grade 0–3). Results The majority of patients (26 [72.2%] of 36) did not present characteristic arthrosonographic findings of an acute arthritis (distension of the capsule and hyperperfusion). Ankle joint effusion was only observed in 9 (25%) of the 36 patients, with a generally mild character (grade I ankle joint effusion: n = 8 [88.8%], grade II ankle joint effusion: n = 1 [11.2%]). In contrast, an extensive subcutaneous edema indicating periarthritis was detected in 23 (92%) of 25 patients. In addition, tenosynovitis could be visualized in 14 patients (38.8%) using MSUS. Conclusion Utilizing MSUS, including power Doppler, the present results clearly demonstrate that ankle swelling in patients with Lofgren's syndrome is predominantly due to periarticular soft tissue swelling and tenosynovitis. In contrast, distinct articular synovitis is rare and if present, only to a mild degree, without relevant power Doppler activity.